Advanced cervical leiomyosarcoma with severe comorbidities: a clinical conundrum for optimal management - Dubey, Pankhuri; Gadre, Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Leiomyosarcoma of uterine cervix constitute a very rare but aggressive group of neoplasms of the cervix with poor prognosis. Although recognised as a distinct entity, treatment algorithms and overall management strategies rely on suggestions from uterine counterparts as robust data on management of the cervical leiomyosarcoma, especially when advanced, is scarce. Present case was a 51-year-old perimenopausal woman with acyclic vaginal bleeding and dyspnoea on ordinary physical activity. On examining, a firm hypogastric mass of 14 weeks was found abdominally and a pedunculated, polypoidal hard mass of 5X5 cm with a 2 cm thick peduncle coming out of endocervical canal (confirmed on CT) was noted hanging outside vagina. Histopathology suggested cervical leiomyosarcoma. Triple vessel disease and severe cardiac dysfunction (LVEF=30%) with large left ventricular thrombus rendered the patient at very high risk for mortality during surgery. Systematic comorbidity assessment with due consideration to risk-benefit ratio of all treatment options was undertaken and neoadjuvant chemotherapy was started after multidisciplinary recommendation. Patient tolerated the first cycle of chemotherapy well but died of a sudden cardiac arrest after one week. Advanced age and stage are poor predictors for survival in patients with aggressive cervical leiomyosarcomas, even more so, in those with severe comorbidities. Meticulous clinical evaluation and systematic incorporation of comorbidity indices in decision-making for tailored cancer treatment is imperative in arriving at a justified plan of action for this rare and aggressive entity.